Do Immediate External Rewards Really Enhance Intrinsic Motivation? - Liu, Yuxia; Yang, Yang; Bai, Xue; Chen, Yujie; Mo, Lei (Frontiers in Psychology, 2022)
Researchers have conducted many studies on the relationship between external rewards and intrinsic motivation. A recent study showed that, compared with delayed rewards, rewards delivered immediately after the experiment enhanced the participants' intrinsic motivation. However, this study did not rule out the possibility of a misattribution effect of extrinsic motivation. The present research conducted 3 studies to explore whether immediate rewards actually enhance intrinsic motivation. To rule out the interference of the misattribution effect of extrinsic motivation, according to the different characteristics of extrinsic motivation and intrinsic motivation, Study 1 and Study 2 improved the prior experimental paradigm, and the results indicated that the intrinsic motivation of participants who received extra-rewards immediately after completing experimental tasks was stronger than that of participants who received the delayed extra-reward. Furthermore, to rule out the potential interference of temporal discounting, Study 3 introduced a new variable—reward magnitude. The results showed that the delivery time of the extra reward had an independent effect on intrinsic motivation and that the immediacy of the extra reward could enhance intrinsic motivation. In all, the 3 studies strongly demonstrated that immediate external extra-rewards could truly enhance intrinsic motivation.